ChemInform Abstract: Glycosides from the Aerial Parts of Patrinia villosa. Issue 12 (25th March 2014) - Lee, Joo Young; Kim, Ju Sun; Kim, Yeong Shik; Kang, Sam Sik
Abstract isolation and structure elucidation of two new flavonoid glycosides, patrivilosides 1 (Ia), 2 (Ib), patrinovalerosidate (II), and two new saponins, patrinovilosides A and B